2009
DOI: 10.1002/ajmg.a.32488
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive profile of disorders associated with dysregulation of the RAS/MAPK signaling cascade

Abstract: Mutations in genes coding for transducers participating in the RAS/MAPK pathway have been identified as the molecular cause underlying a group of clinically related developmental disorders with cognitive deficits of variable severity. To determine the spectrum of cognitive defects associated with dysregulation of this signal cascade, we studied the profile of cognitive abilities in patients with mutations affecting the PTPN11, SOS1, HRAS, KRAS, BRAF, RAF1, and MEK1 genes and phenotype-genotype correlations. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
87
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 54 publications
(79 reference statements)
8
87
0
3
Order By: Relevance
“…In one study, intellectual functioning of children with SOS1 mutations was found to be significantly higher than those with PTPN11 mutations, as well as those with unknown mutations (Pierpont et al 2009), although the sample size of the SOS1 mutation group was relatively small. This finding is consistent with other reports suggesting that, in the absence of complicating neurological features such as seizures, most people with SOS1 mutations have intellect within the average range and attend regular education classrooms (Tartaglia et al 2007;Cesarini et al 2009). In general, behavioral and adaptive functioning of children with SOS1 mutations tends to be consistent with those with PTPN11 mutations and those of other children with a clinical diagnosis of NS (Pierpont et al 2010b;Pierpont et al 2015;Alfieri et al 2014).…”
Section: Relationship Between Genotype and Neurocognitive Outcomessupporting
confidence: 93%
See 4 more Smart Citations
“…In one study, intellectual functioning of children with SOS1 mutations was found to be significantly higher than those with PTPN11 mutations, as well as those with unknown mutations (Pierpont et al 2009), although the sample size of the SOS1 mutation group was relatively small. This finding is consistent with other reports suggesting that, in the absence of complicating neurological features such as seizures, most people with SOS1 mutations have intellect within the average range and attend regular education classrooms (Tartaglia et al 2007;Cesarini et al 2009). In general, behavioral and adaptive functioning of children with SOS1 mutations tends to be consistent with those with PTPN11 mutations and those of other children with a clinical diagnosis of NS (Pierpont et al 2010b;Pierpont et al 2015;Alfieri et al 2014).…”
Section: Relationship Between Genotype and Neurocognitive Outcomessupporting
confidence: 93%
“…A number of studies have shown that mutations in genes acting more downstream in the RAS-MAPK pathway (e.g., BRAF, MEK 1, MEK2, HRAS), which typically cause CFC syndrome and Costello syndrome, tend to be associated with greater impairments in neurological, intellectual, and adaptive functioning than mutations in genes encoding components or regulators that act more upstream in the pathway (e.g., NF1, PTPN11, SOS1, RAF1), which cause NF1 and NS (Cesarini et al 2009;Pierpont et al 2010b;Yoon et al 2007). Individuals with gene mutations acting downstream in the pathway (especially those diagnosed with CFC syndrome) also tend to have a higher prevalence of autisticlike traits (Adviento et al 2014;Alfieri et al 2014).…”
Section: Relationship Between Genotype and Neurocognitive Outcomesmentioning
confidence: 99%
See 3 more Smart Citations